Österreichische Historiker, Band 3 Lebensläufe und Karrieren 1900-1945, Band 3 - Hruza, Karel (f1fc2385-b4e1-45d0-860d-d3f2b24f0557, 2019)
The book presents detailed scientific biographies of 13 Austrians historians from the period 1900-1945. It focuses on the scientific work, careers and political activities and their changes